Damage Control Management in the Polytrauma Patient - Pape, Hans-Christoph.; Peitzman, Andrew; Schwab, C. William; Giannoudis, Peter V.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Damage control surgery was developed as a management technique for severely injured patients whose immune systems are too weak to mount an adequate response to multiple extended procedures. The common goal of treating life-threatening conditions first, then treating major pelvic and extremity fractures requires cooperation between all major subspecialties involved in the care of polytrauma patients. The editors of this book have focused on approaching damage control surgery logically and systematically by dividing treatment into phases. Other vital topics discussed include patient selection, management of vascular injuries, and the timing of secondary definitive procedures. Damage Control Management in the Polytrauma Patient is an unparalleled resource for any clinician who must weigh life-saving operations against limb-threatening conditions.
Epidemiology and Pathophysiology -- The Damage Control Approach -- Epidemiology of Polytrauma -- Pathogenetic Changes: Isolated Extremity Trauma and Polytrauma -- Pathogenetic Changes: Secondary Abdominal Compartment Syndrome -- Impact of Head and Chest Trauma on General Condition -- Patient Selection: Orthopedic Approach in Isolated Injuries -- Patient Selection: Orthopedic Approach in Polytrauma -- Phases of Damage Control -- Phase 0: Damage Control Resuscitation in the Pre-hospital and Emergency Department Settings -- Phase I: Abbreviated Surgery -- Phase II: The ICU Phase of Damage Control: Managing the Patient from Door to Door -- Phase III:?Second Operation Repair of All Injuries General and Orthopedics -- Phase IV: Late Reconstruction Abdominal Wall Closure: Staged Management Technique -- Phase IV: Late Reconstruction: Reconstruction of Posttraumatic Soft Tissue Defects -- The Role of Interventional Radiology -- Special Aspects of Damage Control -- Head Injuries in Polytrauma Patients -- Spinal Injuries in Polytrauma Patients -- Pelvic Fractures in Polytrauma Patients -- Vascular Injuries in Polytrauma Patients -- Pediatric Trauma and Polytrauma Pediatric Patients -- Damage Control in Elderly Polytrauma Patients -- Mass Casualties: Military and Civilian -- Complications and Outcomes -- Complications and Outcomes: Abdominal, General, and Extremity Complications -- Critical Decision Points in Managing the Open Abdomen -- Functional Long-Term Outcomes in Polytrauma Patients with Orthopedic Injuries.
Keywords: Medicine; Emergency medicine; Orthopedics; Surgery; Trauma; Medicine & Public Health; Orthopedics; Traumatic Surgery; Emergency Medicine; General Surgery